2008
DOI: 10.3998/ark.5550190.0009.404
|View full text |Cite
|
Sign up to set email alerts
|

Monocyanomethylated thiacalix[4]arenes: synthesis and lower rim modification

Abstract: The selective monocyanomethylation of p-R-thiacalix [4]arenes (R = H, tert-Bu) with chloroacetonitrile in the presence of Na 2 CO 3 in DMF is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Adamantane-1,3-diol is known [19,20] to act as a bi electrophile in the adamantylation of carbon-and nitrogen-centered nucleophiles in TFA; however, the use of more available and cheaper 1,3-dibromoadaman- tane for this purpose seemed more attractive. We previously showed that 1-bromoadamantane in boiling TFA is quantitatively converted to adamantan-1-yl trifluoroacetate and that it can be used for the adamantylation of various nucleophiles [21].…”
Section: Resultsmentioning
confidence: 99%
“…Adamantane-1,3-diol is known [19,20] to act as a bi electrophile in the adamantylation of carbon-and nitrogen-centered nucleophiles in TFA; however, the use of more available and cheaper 1,3-dibromoadaman- tane for this purpose seemed more attractive. We previously showed that 1-bromoadamantane in boiling TFA is quantitatively converted to adamantan-1-yl trifluoroacetate and that it can be used for the adamantylation of various nucleophiles [21].…”
Section: Resultsmentioning
confidence: 99%